Moda, consumo e biossociabilidade : convocações para a gestão do corpo diferente em narrativas publicitárias de moda - Merten, Luíza Ribeiro (2017)
This research selects as themes the discourses about the different body in advertising narratives of two large retail chains of Brazilian fashion, produced and run between 2012 and 2015. From the research of the discourse of fashion retail chains, taking into account their conditions of production, In this paper we sought to answer the problem question: how fashion advertising narratives call for the management of the different body in the light of the notion of biossociabilities of consumption? As objective of problematizing the phenomenon of consumption, especially in fashion, we will develop a reflection on the management of the different body in the contemporary advertising discourse, from of the theoretical-methodological conduct of French Speech Analysis. Theoretical framework is organized in three axes: the first refers to the Communication and Consumer interfaces in the contemporaneity - for which we seek contributions in authors such as Silverstone, Baccega, Hoff and Rock; the second refers to French Speech Discourse Analysis, and is constructed from authors such as Gregolin and Orlandi; and the third considers the Body, Fashion and Biossociability. On this axis, we start from some scholars of Foucault's thinking, such as Rabinow and Ortega, who, based on the philosopher's reflections, propose the concept of biossociability and also in Hoff, which proposes reflections on the biossociabilities of consumption. Our empirical object is calls for the management of the different body, analyzed in a corpus consisting of eight videos C & A and Marisa brands, who had images of "different body" and in which the difference was stated. In our methodology, we describe the eight videos, identifying the main signs related to the physical beauty of the consumer-characters and their style of life expressed in the narrative. We also map the meanings attributed to the different body and calls for the management of this, characterizing strategies of production of meanings of difference in images of the aesthetic body in the narrative of advertising, which we relate to memory discourse and interdiscourse. And, from the identification of sayings and non-sayings, we investigate the calls for management of the body different in the contemporary - standards of beauty / thinness; personal achievements / career; affirmation / representation of groups / symbolic capital - in the light of concept of biossociability. In our analysis, we relate the presence and exaltation of bodies different in these narratives to the social and economic changes of contemporary Brazil, observing, on the one hand, the economic interest of brands for new consumer audiences and, on the other hand, symbolic dispute that occurs in the confrontations of the discourses in the media, notably debates on the way the media edits the world - "Press" the advertising narrative of fashion to resignify or change their strategies. The results demonstrated that: 1) biopolitical calls generate logics of consumption; 2) the Fashion advertising narratives promote biossociability, as they institutionalize the dress and call for the management of groups whose bodies we call different.